Islamic Financial Literacy and the Utilization of Islamic Microfinance Products A Phenomenological Study of Low-Income Communities in Geragai District - Baharudin; Wargo; Kuswanto (Zabags International Journal of Economy, 2026)
Low levels of Islamic financial literacy among low- to middle-income communities remain a major challenge in optimizing the utilization of Islamic microfinance products. This condition often leads to pragmatic usage patterns that do not fully reflect an understanding of the underlying Sharia principles and contractual mechanisms. This study aims to examine in depth the level of Islamic financial literacy within the community and its relationship with the utilization of Islamic microfinance products. The research adopts a qualitative approach with a phenomenological design, focusing on the lived experiences and subjective interpretations of low-income community members as users and prospective users of Baitul Maal wat Tamwil (BMT) and Islamic cooperatives in Geragai District. Primary data were collected through observation, in-depth interviews, and documentation, and analyzed using source and method triangulation techniques. The findings indicate that community-level Islamic financial literacy remains at a basic level, particularly regarding the understanding of Sharia principles and akad (Islamic contracts), which significantly influences utilization patterns that are largely functional rather than optimal. These results underscore the importance of contextual, community-based Islamic financial education in strengthening sustainable Islamic financial inclusion and contribute empirically to the growing body of literature on Islamic financial literacy grounded in community experience.